Walk the line: a systemic perspective on stress experienced by emergency medical personnel by comparing military and civilian prehospital settings - Martine Van Puyvelde; Martine Van Puyvelde; Martine Van Puyvelde; Martine Van Puyvelde; Jolien Van Herck; Jeroen Van den Bossche; Frederic Goethals; Daisy Gijbels; Frederic Detaille; Nathalie Pattyn; Nathalie Pattyn; Nathalie Pattyn (Frontiers Media S.A., 2023)
IntroductionEmergency Medicine (EM) personnel in both military and civilian prehospital settings are often exposed to stressful and extreme events. Therefore, a cross-pollination between both contexts in terms of coping strategies may generate new information for purposes of training, prevention, and support programs. In the current study, we aimed at comparing both contexts to understand the type of stress events personnel experience; whether experience differs between civilian and military personnel; and how they cope with it.MethodsWe used a mixed method approach, combining the results of a quantitative questionnaire and a thematic analysis of 23 in-depth semi-structured interviews to gain additional qualitative information.ResultsWhereas the questionnaire pointed to a significant preference for task-oriented coping over avoidant and emotion-oriented coping, the interviews offered a more nuanced insight, showing a constant aim to position themselves on a continuum between emotional disconnection from the patient to preserve operationality on the one hand; and remaining enough empathic to preserve humanity on the other hand. We further identified an ambivalent awareness regarding emotions and stress, a vulnerable disbalance between an excessive passion for the job with the sacrifice of own's personal life (for a growing volatile and dangerous working environment) and a lack of recognition from both the patient and organizational environment. The combination of these factors may carry the risk for moral injury and compassion fatigue. Therefore, mutual trust between the organizational level and EM personnel as well as among team members is crucial.DiscussionThe results are discussed from a systemic SHELL perspective, indicating how the specific profile of EM personnel relates to the software, hardware, environmental and liveware components of their professional and private life. Trainings on stress- and risk awareness should be approached both on an individual and systemic level, knowing that there is clearly no "one-size-fits-all" manner.